Radiolaria and Phaeodaria (siliceous Rhizaria) in south-western and northern Norwegian fjords during late summer 2016: dominant species and biomass in shallow-water assemblages - Takahito Ikenoue; Kjell R. Bjørklund; Anders K. Krabberød; Shigeto Nishino; Paul Wassmann (Polar Research, 2023)
To determine the present-day community composition of siliceous Rhizaria (Radiolaria and Phaeodaria) in Norwegian fjords, plankton tows were conducted in south-western and northern Norwegian fjords in September 2016. The mean total abundance of radiolarians was 306 m–3 in the Sognefjord complex, which was the southern research site, and, in the north, 945 m–3 in Malangen and 89 m–3 in Balsfjord, both above the Arctic Circle. Sticholonche zanclea was the most abundant radiolarian in the Sognefjord complex and Malangen, accounting for 78–100% (mean 89%) of radiolarian abundance. The mean total abundance of phaeodarians was 1554 m–3 in the Sognefjord complex, 51 m–3 in Malangen and 11 m–3 in Balsfjord. Medusetta arcifera was the most abundant phaeodaria in the Sognefjord complex, accounting for >99% of phaeodarian abundance, but was absent in Malangen and Balsfjord, where Protocystis tridens accounted for >96% of phaeodarian abundance. The carbon biomass of S. zanclea and M. arcifera was 188 and 438 µg C m–3, respectively, which is similar to and 8.6 times higher than, respectively, that of phaeodarians >1 mm in the western North Pacific, suggesting that M. arcifera contributes to organic carbon transport in the Sognefjord complex. Amphimelissa setosa (Nassellaria, Radiolaria), which was a dominant species in the study area in 1982–83, was absent in the present study in all sampled fjords. This could have been caused by the approximately 2 °C increase in water temperature that has occurred since 1990 and can be taken as evidence of a climate-change-associated local temperature rise linked to the warming of advected Atlantic Water.